An alternative approach to CB radio using point-to-point communications. (1st January 2012) - Morgan, Y.L.; Kunz, T.; Seenappa, S.
In this paper we experiment with the modern point-to-point communication approach and redesign it to fulfil the classical application of serving Citizen Band (CB) radio. We provide a novel approach that utilises the modern Dedicated Short-Range Communications (DSRC) as highlighted for vehicular communications. Our approach involves establishing higher quality service for CB streaming traffic. We provide a system to use the heavy vehicle as a gateway for streaming traffic. We utilise the SWAN approach then we improve it by implementing a destination-based approach for real-time traffic regulation. We compare the destination-based regulation with the network-based regulation. We evaluate the impact of applying the enhanced SWAN model by testing the performance of both real-time and best-effort traffic. Finally, we comment on how the real-time streaming traffic service was enhanced without measurable impact on the best-effort services.